Advancing therapeutic applications of gene editing.
Following a rocky start, gene therapy has resurfaced with solid gene transfer solutions that could expand its applications from the treatment of primary immune-deficiencies to the treatment of cancer. The scope of genetic engineering has recently broadened from gene replacement to targeted gene editing using engineered nucleases, which enable precise sequence modification of a locus of interest.